Fabrication and characterization of optically transparent holmium doped yttrium oxide ceramics - Cheong, Debbie Hui Ting (2014)
Transparent Polycrystalline ceramics are excellent materials for hosting solid-state lasers due their advantages in fabrication and flexibility in designing dopant concentrations. The search for the most optimal fabrication route and conditions is widely observed in current research in the field of advanced materials.